2010
DOI: 10.1017/s0950268810002803
|View full text |Cite
|
Sign up to set email alerts
|

Outbreak of acute gastroenteritis caused by adenovirus type 41 in a kindergarten

Abstract: In response to an alert due to epidemic gastroenteritis in children in a kindergarten, an outbreak investigation was carried out in a Portuguese municipality. The objectives were to establish an aetiological diagnosis, assess vaccine efficacy if possible, and to take corrective measures if necessary. The warden at the kindergarten was interviewed, and we visited the premises. The overall attack rate was 11·4% and most cases were mild. Stool samples from three symptomatic children were collected and screened fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…Overall, the HAdV‐positive rate was 5.5% (113/2064), which is lower than that found in a previous study (8.7%; 20/231) in Korea during 1998–1999 (33). Although earlier studies reported that the incidence of HAdV‐40 and HAdV‐41 infections in acute gastroenteritis is similar (34, 35), more recent studies have reported a predominance of HAdV‐41 (17, 29, 36, 37).…”
Section: Discussionmentioning
confidence: 94%
“…Overall, the HAdV‐positive rate was 5.5% (113/2064), which is lower than that found in a previous study (8.7%; 20/231) in Korea during 1998–1999 (33). Although earlier studies reported that the incidence of HAdV‐40 and HAdV‐41 infections in acute gastroenteritis is similar (34, 35), more recent studies have reported a predominance of HAdV‐41 (17, 29, 36, 37).…”
Section: Discussionmentioning
confidence: 94%
“…AdVs may cause epidemics of febrile respiratory illness (FRI), pharyngoconjunctival fever, 45 keratoconjunctivitis (KC), [46][47][48][49] or gastroenteritis and diarrheal illness. [50][51][52][53][54][55][56][57][58][59][60][61] Severe or disseminated AdV infections may occur in immunocompromised hosts 7,9,[62][63][64] and rarely in immunocompetent patients. 23,65 Most epidemics occur in the winter or early spring, 6 but infections occur throughout the year with no clear seasonality.…”
Section: Epidemiologymentioning
confidence: 99%
“…161 Severe and disseminated AdV infections, although rare in the immunocompetent host, 162,163 can occur in immunocompromised patients. [164][165][166][167][168][169][170][171][172][173][174][175] Augmented immunosuppression, including exposure to cytolytic therapies, is considered to be a risk factor for more severe disease in patients who experience AdV infection. 161 AdV infections are typically caused by exposure to infected respiratory secretions through person-to-person contact.…”
Section: Adenovirus Epidemiology and Transmissionmentioning
confidence: 99%